Enabling an effective knowledge and information flow between the phases of building construction and facilities management - Tan, A.; Zaman, Atiq; Sutrisna, Monty (Emerald Group Publishing Ltd., 2018)
Purpose The purpose of this study is to investigate ways of transferring knowledge and information during the life-cycle phases of construction projects, particularly between the construction and occupancy phases, and to find an approach to minimise knowledge and information gaps during the handover process. Design/methodology/approach The study applied a qualitative approach involving a literature review and an archival analysis of information flow in the studied cases of a construction project, followed by a cross-cases analysis and expert interviews. Data on information flow were collected from three cases of building construction projects in Perth, Western Australia. In addition, a total of 18 local facilities management experts were interviewed to identify the key reasons of knowledge and information gaps and to propose an effective knowledge flow model. Findings The findings of this study indicated a significant knowledge and information gap, which exists during the handover process in construction projects in Western Australia. The findings of case analysis and expert interviews identified that the project handover guidelines were often ignored in construction projects in Western Australia, and the handover phase was not given the same priority as the design and construction phases by most of the project stakeholders, which led to information and knowledge gaps between the project construction and post-occupancy phases. The study conducted, integrated knowledge and information flow modelling to analyse the knowledge and information gaps followed by mapping the gaps against existing knowledge sharing frameworks (KSFs) before proposing an integrated knowledge sharing conceptual model to improve current practice and to enhance the information flow during the various phases of the construction project life cycle. Research limitations/implications The study is based on three cases in Perth, Western Australia, and thus the findings and recommendations are contextual. Whilst laying a good foundation to do so, further research is needed to investigate more cases in Western Australia and beyond to fully generalise the findings from this study. Originality/value The study contributes to improve the handover process and information flows in project life-cycle phases in Western Australia and develop an information flow model followed by bringing together existing KSFs, namely, the open communication channel (OCC), soft landing framework (SLF) and building information modelling (BIM), to propose an integrated knowledge sharing conceptual model. The methodology used here to analyse the information flow in a diagrammatic manner, the mapping of FM issues against the KSFs’ capabilities and a conceptual model to facilitate change in the industry’s silo mindset are the main contributions of this paper.